Does floor surface affect locomotion behaviour of crossbred cows under loose housing system? - UPADHYAY, DEEPAK; SINGH, MUKESH; GAUR, G K; PATEL, B H M; VERMA, M R; BHARTI, P K; DUTT, TRIVENI (The Indian Journal of Animal Sciences, 2017)
Present study was conducted to evaluate the effect of floor surface on lameness score and walking speed of crossbred cows under loose housing system. Crossbred cows (24) were selected and randomly assigned into one of the four groups (6 in each group) having different combination of flooring surface viz. T0-Concrete floor (in covered feeding area) + Brick paved (in open area), T1-Concrete (in covered feeding area) + Sand bed (in open area), T2- Rubber mat (in covered feeding area) + Sand bed (in open area) and T3- Rubber mat (in covered feeding area) + Brick paved (in open area). All experimental animals were scored for lameness using â€œVisual Lameness Scoringâ€ (VLS) system on 1-5 scale. Walking speed of cows was also observed during experimental period. Lameness scores were significantly different between the groups. Lameness score were greater for cow housed in T3 and T0 group. However, lameness score were lower in cows housed in T1 and T2 group. Walking speed differed significantly between treatments and was greater in T2 and T1 than T3 and T0. Cow housed in T0 and T3 group walked slower compared to T1 and T2 group. Further, proportionally greater numbers of cows with higher lameness score were found in T0 and T3 group. It can be concluded that equipping open area with sand bed with either concrete or rubber mat in covered area improved animal welfare in term of decreasing lameness. While providing rubber mat alone with brick was comparable to concrete and brick.